2019
DOI: 10.4149/neo_2018_181212n957
|View full text |Cite
|
Sign up to set email alerts
|

NKAP plays an oncogenic function partly through AKT signaling pathway in hepatocellular carcinoma

Abstract: NF-κB activating protein (NKAP) is a highly conserved protein involved in transcriptional repression, immune cell development, maturation, T cell acquisition of functional competency and maintenance of hematopoiesis. Here, we first explore the function of NKAP in hepatocellular carcinoma (HCC). We found that NKAP was highly expressed in HCC tissues and associated with a poor patient survival. CCK8 assay showed that NKAP knockdown significantly decreased cell viability of HuH7 and Hep3B HCC cell lines. Cell inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The antiapoptotic (Bcl-2, Bcl-XL) and proapoptotic proteins (BAX, Bid and Caspases). The BAX/Bcl-2 ratio is considered a measure of cell susceptibility to apoptosis [28] as well as proapoptotic index [29]. This ratio was found to be significantly decreased in the current study as reported earlier and may be due to the increased apoptosis via increasing proapoptotic Bax and decreasing antiapoptotic Bcl-2 expression in an animal model [30,31].…”
Section: Discussionsupporting
confidence: 76%
“…The antiapoptotic (Bcl-2, Bcl-XL) and proapoptotic proteins (BAX, Bid and Caspases). The BAX/Bcl-2 ratio is considered a measure of cell susceptibility to apoptosis [28] as well as proapoptotic index [29]. This ratio was found to be significantly decreased in the current study as reported earlier and may be due to the increased apoptosis via increasing proapoptotic Bax and decreasing antiapoptotic Bcl-2 expression in an animal model [30,31].…”
Section: Discussionsupporting
confidence: 76%
“…NKAP was highly expressed in HCC tissues. And NKAP promoted the proliferation and invasion in HCC cell through AKT signaling pathway [40]. Zhao et al discovered that YTHDF1 was significantly upregulated in HCC and positively related to pathological stage.…”
Section: The M6a "Readers" and Hccmentioning
confidence: 99%
“…FADD association with NKAP in the nucleus would stabilize the latter, therefore contributing to its role as a transcriptional repressor able to hamper NOTCH-mediated transcriptional activation. High levels of NKAP have been observed in most tumor types (), and it has been described as an oncogene in hepatocellular carcinoma [141], glioma [142], and breast cancer [143], even as an unfavorable prognostic indicator in the latter (). FADD downregulation in certain cancer types—such as T-LBL—might result in the reduced stability of NKAP complexes in the nucleus, contributing to NOTCH hyperactivation frequently found in T-cell lymphoblastic neoplasms [144].…”
Section: The Roles Of Fadd and Their Participation In Cancermentioning
confidence: 99%